PERAN LINGKUNGAN SEKOLAH DALAM PEMBENTUKAN KARAKTER ANAK USIA DINI - Imron Nugroho Saputro; Eko Sudarmanto; Titis Pambudi; Muhad Fatoni; Rinaldy Adidtya; Amanda Eka Rismawati (STKIP Subang, 2026)
Early childhood character development is a crucial focus in modern education because social changes and the learning environment shape children's moral values and social behavior. The school environment is viewed as a key factor in character formation through social interactions, the instilling of values, and the role models of teachers. This study aims to analyze the role of the school environment in early childhood character development within the context of religious-based elementary education. The study employed a quantitative, descriptive-correlational design with early elementary school students as participants. The research instrument used a teacher observation scale to assess character dimensions, including discipline, responsibility, empathy, cooperation, honesty, and independence. Data were analyzed using descriptive statistics, Pearson correlation, and linear regression to identify the relationship between the quality of the school environment and student character development. The results indicate that a positive school environment contributes significantly to children's character development through a school culture that supports the instilling of moral values ​​and constructive social interactions. These findings underscore the importance of strengthening the school climate as a primary strategy in character education for early childhood.